Hubungan aktivitas fisik dengan kebugaran jasmani siswa SMA Negeri 1 Driyorejo - Muhammad Ilham Setyo Nugroho; Nur Ahmad Arief; Junaidi Budi Prihanto (Physical Education Departement of University PGRI Jombang, 2026)
Research Problems: The influence of a sedentary lifestyle among high school students has raised concerns about its potential to reduce their level of physical fitness. Since the COVID-19 pandemic began, many students have adopted sedentary habits. This sedentary lifestyle, which results in low levels of physical activity, is often associated with decreased physical fitness. Therefore, the purpose of this study was to determine the relationship between the level of physical activity and the physical fitness of students at SMA Negeri 1 Driyorejo. Methods: This study employed a quantitative, non-experimental correlational design. The participants consisted of eleven learning groups of twelfth-grade students selected through a random sampling technique, resulting in a total of 103 respondents. The instruments used for data collection were the International Physical Activity Questionnaire (IPAQ) and the Tes Kebugaran Pelajar Nusantara (TKPN). Statistical analyses included both descriptive and inferential approaches in order to identify the relationship between the variables of physical activity and physical fitness. Results: The findings, based on Spearman’s correlation analysis, indicated that students’ physical activity was not significantly associated with their physical fitness (p = 0.311). This implies that students’ physical activity levels did not have a significant effect on their physical fitness. Conclusion: Based on these results, it can be concluded that factors other than physical activity may influence students’ fitness levels. These factors include dietary habits, sleep duration, daily routines, frequency of gadget use, and various environmental conditions.